Kajian Falsafah Aboge dalam Sistem Ruang Hunian di Kota Cirebon - Mochamad Ghiffary; Ina Helena Agustina (UNISBA Press, 2022)
Abstract. Indonesia has many ancient philosophies, one of which is in the city of Cirebon which has other important cultural sources. Cirebon has historical evidence that comes from cultural heritage that is local but intangible or intangible. In Cirebon itself, the concept of the embodiment of residential space emerged, namely in the Aboge Philosophy. The purpose of this study is to describe the Aboge philosophy in the residential space system. The approach and analysis method used in this research is to use the hermeneutic approach. In the Aboge philosophy there is a balance between humans, God, and the environment, which is shown through the elements of time, the layout of a room, the direction of the wind, and holding rituals, all of these elements are an effort to get rid of negative energy in the construction of a dwelling. The aboge philosophy that exists and develops in the city of Cirebon is intengible, but this is still maintained by some people and the Cirebon palace by means of